Integrative multi-omics analysis identifies FAM3D as a prognostic tumor suppressor in cervical cancer - Yanbin Chen; Yu Hong; Dongjun Wei; Lianjiao Fan; Dian Tao; Rui Zhang; Hongwei Yang (Functional & Integrative Genomics, 2026)

Comparative study of the toxic effects of polystyrene microplastic particles of different sizes on the livers of pearl gentian grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Hongyue Shi; Meichen Liu; Xiaohan Yang; Yijiang Luo; Zhenzhen Fang; Yanbin Ji; Chengxun Chen; Yanli Liu; Xueliang Sun; Wenwen Yu (Marine Pollution Bulletin, 2026)

Milk exosomal miRNA cargo is remodeled during dietary trans-10, cis-12 CLA-induced milk fat depression in Holstein cows - Jingna Yang; Mingyue Hu; Yifan Fang; Yingqian Han; Yanbin Yang; Yu Sun; Kun Pang; Liqiang Han (International Dairy Journal, 2026)

Valorization of bigeye tuna (Thunnus obesus) bone by-products via steam explosion: Novel umami peptides with synergistic taste enhancement and sodium reduction potential - Yi-Qi Zhang; Chengcheng Li; Lai Wei; Dongcheng Li; Xinyi Yu; Jiajia Wu; Zhiyuan Dai; Yanbin Lu (Food Chemistry, 2026)

Breaking biofilm barriers and reprogramming immunity: NIR-activated protease–copper nanozymes drive cuproptosis-like killing and accelerate infected wound repair - Yi Hu; Zijian Hu; Yuting Ding; Yuan Zhou; Duo Zhou; Song Ye; Wei Jiang; Yanbin Zhang; Junhui Song; Chengying Meng; Yu Chen; Yueyang Fang; et al. (Chemical Engineering Journal, 2026)

Trace element-driven regulation of cordycepin and pentostatin biosynthesis in Cordyceps militaris - Bingjie Zhao; Ruoyu Zhao; Yong Zhang; Xiaotong Li; Jinlei Shi; Yu Li; Yanbin Guo (Food Bioscience, 2026)

Multi-batch treatment of swine slaughterhouse wastewater by microalgal–fungal consortium system: Stability and effects on dissolved organic matter - Zhengsheng Shi; Yequan Sheng; Xin Tan; Yu Xin; Xiaolong Wu; Qin Zhang; Yanbin Li (Environmental Research, 2026)

Preparation and properties of a sodium alginate based gel for dust suppression and moisture regulation - Yanbin Yu; Sai Li; Xiaosong Hou; Bo Zhou; Wenting Cui; Lianxin Fang; Kai Li (Sustainable Chemistry and Pharmacy, 2026)

Top-down trophic cascade effects on the restoration of ecological functions in heavy-metal-contaminated soils: Multi-trophic level regulation aggravates microbial metabolic limitation - Yanbin Du; Caihong Yu; Yuyan Zhu; Yijia Liu; Ying Shen; Rongrong Ma; Qiao Yang (Applied Soil Ecology, 2026)

Metabolomic profiling and identification of flavonoids related compounds in peanut seed oils for inhibition of aspergillus flavus growth - Lingling Wu; Weinan Xu; Xinyang Wang; Muhammad J. Umer; Weicai Jin; Zhihui Sun; Shaoxiong Li; Yanbin Hong; Rajeev K. Varshney; Lu Huang; Runfeng Wang; Qianxia Yu; et al. (Food Chemistry, 2026)

Viscosity and structure of hydrous silicate liquids: Constraints on oceanic hydrothermal circulation - Qi Chen; Craig Lundstrom; Yanchong Li; Young Jay Ryu; Tony Yu; Stella Chariton; Dongzhou Zhang; Vitali Prakapenka; Yanbin Wang (Earth and Planetary Science Letters, 2026)

Study on seepage characteristics of coal fracture networks based on fractal theory and micro-CT - Wenting Cui; Yanbin Yu; Weimin Cheng; Jie Zang; Zihao Yuan (Bulletin of Engineering Geology and the Environment, 2026)

Spatiotemporal Patterns, Driving Mechanisms and Responses of Soil Drought to Meteorological Drought in the Yellow River Basin of China - Fei Wang; Wenhan Yu; Yi Zhang; Hexin Lai; Mengting Du; Qian Xu; Rong Li; Ruyi Men; Haoyu Li; Kai Feng; Shikai Gao; Yanbin Li; et al. (International Journal of Climatology, 2026)
With the escalation of global warming, the potential for land evaporation in the Yellow River Basin (YRB) has increased remarkably, and the problem of soil drought has become increasingly prominent. This not only restricts the development of the agricultural economy in the basin, but also intensifies the disparity between water availability and demand, and exerts a profound influence on the ecological security of the basin. In light of this, this study focuses on soil moisture in the YRB from 2000 to 2022, and conducts an in‐depth analysis of the temporal evolution, spatial patterns, abrupt change characteristics as well as the driving forces of soil drought by calculating the Standardised Soil Moisture Index (SSMI). The results show that: (1) Soil drought in the YRB from 2000 to 2022 exhibited a decreasing trend. A negative abrupt change point occurred in February 2004, indicating a sudden intensification of arid conditions. The soil drought in the Above Longyangxia (AL) region exhibited the most significant decreasing trend in September. (2) The most severe soil drought occurred in 2006, and the drought was most intense in November of that year, when the drought‐affected area reaching 86.96%. The severely drought‐stricken areas were predominantly concentrated in the central and northern regions of the basin. (3) The SSMI in the second‐level sub‐regions of the YRB exhibits three types of abrupt changes: increase to decrease, intermittent increase, and decrease to increase, and shows a clear trend from upstream to downstream. (4) The results of cross‐wavelet analysis indicate that soil moisture‐absolute humidity‐soil temperature is the best explanatory combination for soil drought. (5) The slopes of the small‐ and medium‐scale fittings in the AL region are 0.5021 and 0.2584, respectively, and the corresponding mean values of meteorological drought severity are 0.87 and 2.57, respectively. Drought events in the YRB are mainly of medium/short duration and low severity, and soil drought severity tends to increase with the intensification of meteorological drought. This study reveals the spatiotemporal variation patterns of soil drought in the YRB, as well as the responses of climate to soil drought. These findings provide a scientific basis for drought resistance and ecological protection within the basin.

River-sea interaction-regulated spatial distribution and source apportionment of mercury in the soil of the Yellow River Estuary coastal wetland - Ziwen Yu; Yingjun Wang; Xiaoquan Liu; Zheng Li; Zhiwei Xie; Yue Guo; Yue Song; Qingzhe Zhang; Yanbin Li; Yongguang Yin; Yong Cai (Marine Pollution Bulletin, 2026)

Hierarchically assembled UiO-66@PIL@PP core-shell catalyst: Synergistic integration of catalysis and CO2 enrichment for efficient cycloaddition - Zhenzhu Tang; Qian Zhang; Baowen Lin; Yunliang Yu; Yanbin Zeng; Chao Zou; Guanqun Xie; Xiaoxia Wang (Journal of Environmental Chemical Engineering, 2026)

Volcanic emissions and diatom blooms enhanced mercury accumulation and methylation in hadal sediments during the last deglacial phase - Zhengwen Zhou; Huiling Wang; Yu Xin; Yingjun Wang; Xiting Liu; Jiwei Tian; Holger Hintelmann; Yongguang Yin; Guangliang Liu; Yong Cai; Yanbin Li (Geochimica et Cosmochimica Acta, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Characteristics of n-heptane conversion by microwave liquid plasma for C2 hydrocarbons production:Effect of reactant volume and pressure - Zhonglin Yu; Bing Sun; Guoxuan Ding; Jinglin Liu; Xiaomei Zhu; Yanbin Xin (Journal of Cleaner Production, 2026)

Study on temperature/oxygen dependence of ammonia-alcohol laminar premixed flame characteristics and N2O generation by highspeed photography and laser Raman spectroscopy - Changyou Yu; Degang Li; Wanchen Sun; Hao Zhang; Peng Cheng; Liang Guo; Yuying Yan; Miao Yang; Yanan Guo; Xiaotian Wang; Yanbin Shi; Changcheng Liu (Fuel, 2026)

Efficacy of alpha-lipoic acid in mitigating neuropathic pain: mechanistic insights and therapeutic implications - Daosong Dong; Yanbin Sun; Qingqing Sui; Zichen Zhao; Hong Ma; Kai Li; Xue Yu (Inflammopharmacology, 2026)

Methylsiloxanes in drinking water treatment plants: Occurrence, removal efficiencies and exposure risks across multiple stages of treatment process development - Yimeng Zhang; Zhenyang Yu; Jing Yang; Ge Yin; Yanbin Zhao; G․Daniel Sheng; Daqiang Yin (Water Research, 2025)

Sustainable extraction and characterization of type I collagen from tuna skin waste utilizing biocompatible ionic liquid-based aqueous two-phase system - Qianqian Chen; Botao Liang; Xuan Yuan; Xinyi Yu; Chengcheng Li; Lai Wei; Jing Ye; Jiajia Wu; Zhiyuan Dai; Yanbin Lu (Food Hydrocolloids, 2025)

In situ deformation of antigorite-olivine two-phase mixtures: Implications for dynamics and seismic anisotropy in the mantle wedge - Rose Hurlow; Wenhao Su; Wen-Yi Zhou; Feng Lin; Lowell Miyagi; Timothy Officer; Tony Yu; Yanbin Wang; Meiqian Wu; Qin Wang; Jin S. Zhang (Earth and Planetary Science Letters, 2025)

Paramylon biorefinery from Euglena gracilis via recyclable aqueous two-phase system: A sustainable platform for high-content β-1,3-glucan production - Jiajia Wu; Xinyi Yu; Lai Wei; Xuan Yuan; Dongcheng Li; Botao Liang; Chengcheng Li; Zhangchi Chen; Yanbin Lu (Carbohydrate Polymers, 2025)

Integrative genomics and genetics from evolutionary insights to precision breeding in peanuts (Arachis Hypogaea L.) - Muhammad Jawad Umer; Lu Huang; Hao Liu; Raufa Batool; Haifen Li; Shaoxiong Li; Yanbin Hong; Runfeng Wang; Qianxia Yu; Qing Lu; Rajeev K. Varshney; Xiaoping Chen (Functional & Integrative Genomics, 2025)

Comparative biofortification of selenite and SeNPs on selenium enrichment and the synthesis of monacolin K and pigments in Monascus ruber - Bingjie Zhao; Xueni Wen; Yong Zhang; Ruoyu Zhao; Yu Li; Yanbin Guo (Food Bioscience, 2025)

Characterization of soil bacterial pathogens in peri-urban zones across population density gradients and land use patterns: insights into pathogen diversity, composition, interactions, and community assembly processes - Wenyao Li; Jiacheng Zou; Caihong Yu; Fuyuan Qiu; Huadong Tan; Yanbin Du; Jinshuai Shi (Environmental Research, 2025)

Constructing CRISPR-Cas9 system for metabolic reprogramming and cordycepin biomanufacturing in Pichia pastoris - Bingjie Zhao; Jinlei Shi; Ruoyu Zhao; Shan Gao; Yu Li; Yong Zhang; Yuquan Wei; Yanbin Guo (Bioresource Technology, 2025)

Phosphorus strategy alters mechanism of microbial stress caused by soil arsenic contamination - Zhanghan Sun; Yanbin Du; Caihong Yu; XiaoXia Liu; Han Wang; Shengtao Shen; Zhiyuan Liu (Journal of Hazardous Materials, 2025)

Discovery of novel umami peptides and their bitterness masking effects from yellowfin tuna (Thunnus albacares) via peptidomics, multisensory evaluation, and molecular docking approaches - Lai Wei; Cui Shi; Dongcheng Li; Xuan Yuan; Xinyi Yu; Botao Liang; Jiajia Wu; Yiqi Zhang; Zhiyuan Dai; Yanbin Lu; Jing Ye (Food Chemistry, 2025)

Late Holocene transition from natural to anthropogenic forcing of fire regime in Arid Central Asia - Guoqiang Ding; Jianhui Chen; Yanbin Lei; Wensheng Zhang; Shuo Wang; Panpan Ji; Yu Cao; Shengqian Chen; Fahu Chen; Heikki Seppä (Science of The Total Environment, 2025)

Salt precipitation and reservoir damage during deep coalbed methane extraction - Xiaoxiao Sun; Chenglin Yu; Chunhu Li; Xiangyu Wang; Hui Wang; Yanbin Yao (International Journal of Coal Geology, 2025)

Continuous site mutagenesis of fatty acid photodecarboxylase enables a highly thermostable enzyme for co-solvent-free decarboxylation - Mingdong Wang; Yu Wang; Haoxian Huang; Xuanyu Cao; Jiangang Ren; Yanbin Feng; Song Xue (Bioresource Technology, 2025)

Distribution of and associations between ARGs and pathogenic bacteria in soils affected by heavy metal contamination in mining areas - Yanbin Du; Yijia Liu; Caihong Yu; Xuesong Hu; Suya Ma; Jiacheng Zou; Ronghua Lin; Yanhua Hou; Menglun Wang; Nan Zhang (Journal of Environmental Chemical Engineering, 2025)

Adsorption of methyl parathion on four various microplastics in aqueous solution: Kinetics, isotherms and molecular dynamics simulations - Yifei Leng; Junhao Li; Jun Liu; Fengyi Chang; Zhu Li; Yu Huang; Wen Xiong; Buyun Wu; Bangding Han; Haolun Chen; Yanbin Zhang; Jun Wang (Gondwana Research, 2025)

Development of a hydraulic variable-diameter threshing drum control system for combine harvester part II: Controller design and field performance - Yanbin Liu; Yaoming Li; Kuizhou Ji; Zhiwu Yu; Zheng Ma; Lizhang Xu; Changhe Niu (Biosystems Engineering, 2025)

Disturbance observer-based composite recoil controller design for deepwater drilling riser systems after emergency disconnection - Hai-Yang Yu; Yan-Dong Zhao; Bao-Lin Zhang; Yanbin Wang; Yan-Long Cao (Ocean Engineering, 2025)

Research on dust suppression technology and structural optimization of cylindrical vortex air curtains based on artificial tornado mechanism - Yanbin Yu; Lianxin Fang; Min Xiang; Wenting Cui; Sai Li; Kezhi Song (Journal of Environmental Chemical Engineering, 2025)

Soil resource availability regulates the response of micro-food web multitrophic interactions to heavy metal contamination - Yanbin Du; Caihong Yu; Zhanghan Sun; Yijia Liu; XiaoXia Liu; Yang Feng; Hongting Wang; Jie Zhou; Xianhong Li (Environmental Research, 2025)

The influences of heavy metals on soil microbial C, N, P cycling and heavy metal resistance under different fertilization regimes - Jingyu Tian; Yanbin Du; Caihong Yu; Wenqing Liu; Ruihong Zou; Yunfeng Zhao; Tao Zhang; Yucong Jiang; Zhijun Tian (Environmental Pollution, 2025)

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Development of a hydraulic variable-diameter threshing drum control system for combine harvester part I: Adaptive monitoring method - Yanbin Liu; Yaoming Li; Kuizhou Ji; Zhiwu Yu; Zheng Ma; Lizhang Xu; Changhe Niu (Biosystems Engineering, 2025)

Sound velocities and thermal equation of state of fcc-iron-nickel alloys at high pressure and high temperature: Implications for the cores of Moon and several planets - Siheng Wang; Sibo Chen; Man Xu; Tony Yu; Yanbin Wang; Baosheng Li (Earth and Planetary Science Letters, 2025)

Spatiotemporal distribution patterns of macrobenthic communities and their relationship with environmental factors in the Shengsi Archipelago (Zhejiang, China) - Lingxiang Jin; Yibo Liao; Peisong Yu; Yanbin Tang; Qinghe Liu; Rongliang Zhang; Lu Shou; Jiangning Zeng; Quanzhen Chen (Acta Oceanologica Sinica, 2025)

Construction waste as a filler of denitrification biofilter for nitrate utilization from wastewater: Characteristics, performance, microbial community and soilless culture - Yinzhou Bao; Lijing Bao; Nan Jiang; Xiaoyang Xu; Fan Yu; Haoyu Xing; Wenpei Ye; Peng Zhou; Yanbin Zhu; Shengyang Zheng; Manhong Huang (Bioresource Technology, 2024)

Low-carbon and overproduction of cordycepin from methanol using engineered Pichia pastoris cell factory - Bingjie Zhao; Yu Li; Yong Zhang; Meixi Pan; Guishen Zhao; Yanbin Guo (Bioresource Technology, 2024)

Yangzheng mixture reversed EMT against hepatocellular carcinoma metastasis via NF-κB/NLRP3/β-catenin pathway - Zhengyan Gong; Xuemei Wang; Yuhong Li; Yixuan Nie; Yu Hu; Yanbin Chen; Xiujuan Peng; Feng Liu; Bingling Dai; Yanmin Zhang (Toxicon, 2024)

Developmental toxicity of an emerging organophosphate ester Bis-(2-ethylhexyl)-phenyl phosphate on embryonic zebrafish: Comparison to 2-ethylhexyl diphenyl phosphate - Haochun Shi; Meng Li; Yu Li; Jierong Chen; Congcong Wang; Yiheng Jin; Kun Zhang; Jiayin Dai; Yanbin Zhao (Science of The Total Environment, 2024)

Additive patterns in near-infrared diffuse reflectance spectra: Implications for product formulation and analysis - Le Zhao; Youyan Liang; Nuohan Zhang; Yanbin Chang; Meijuan Fan; Cong Wang; Beibei Li; Hongbo Wang; Yu Liu; Hongxiao Yu; Song Yang; Fuwei Xie; et al. (Food Control, 2024)

Transformational faulting in Mn2GeO4 from olivine to wadsleyite structure: Implications for physical mechanism of deep-focus earthquakes - Feng Shi; Yanbin Wang; Timothy Officer; Dongdong Yao; Tony Yu; Lupei Zhu; Jianguo Wen; Junfeng Zhang; Zhigang Peng (Tectonophysics, 2024)

A binary-medium-based constitutive model for rocks under cyclic loading - Ziyin Cai; Enlong Liu; Di Yu; Bo Xiang; Yunyong He; Yanbin Chen (Computers and Geotechnics, 2024)

Progressive failure characteristics of coal under uniaxial compression: A comprehensive application of micro-ct and digital volume correlation - Yanbin Yu; Chuanwen Ni; Wenting Cui; Weimin Cheng; Yongtao Chen (Bulletin of Engineering Geology and the Environment, 2024)

Overflow of Siling Co on the central Tibetan Plateau and its environmental impacts - Yanbin Lei; Jing Zhou; Tandong Yao; Broxton W. Bird; Yifan Yu; Shujin Wang; Kun Yang; Yinsheng Zhang; Jianqing Zhai; Yufeng Dai (Science Bulletin, 2024)

Finite element analysis of a new preoperative traction for cervical kyphosis: suspensory traction - Hongyu Chen; Tianchi Wu; Shengfa Pan; Li Zhang; Yanbin Zhao; Xin Chen; Yu Sun; William W. Lu; Feifei Zhou (Medical & Biological Engineering & Computing, 2024)
A finite element model of cervical kyphosis was established to analyze the stress of cervical spine under suspensory traction and to explore the mechanism and effect of it. A patient with typical cervical kyphosis (C2-C5) underwent CT scan imaging, and 3D slicer was used to reconstruct the C2 to T2 vertebral bodies. The reconstructed data was imported into Hypermesh 2020 and Abaqus 2017 for meshing and finite element analysis. The changes of the kyphotic angle and the von Mises stress on the annulus fibrosus of each intervertebral disc and ligaments were analyzed under suspensory traction conditions. With the increase of suspensory traction weight, the overall kyphosis of cervical spine showed a decreasing trend. The correction of kyphosis was mainly contributed by the change of kyphotic segments. The kyphotic angle of C2-C5 was corrected from 45° to 13° finally. In cervical intervertebral discs, the stress was concentrated to anterior and posterior part, except for C4-5. The stress of the anterior longitudinal ligament (ALL) decreased from the rostral to the caudal, and the high level von Mises stress of the kyphotic segments appeared at C2-C3, C3-C4, and C4-C5. The roles of the other ligaments were not obvious. The kyphotic angle was significantly reduced by the suspensory traction. Shear effect due to the high von Mises stress in the anterior and posterior parts of annulus fibrosus and the tension on the anterior longitudinal ligament play a role in the correction of cervical kyphosis. Graphical Abstract

Threshing cylinder unbalance detection using a signal extraction method based on parameter-adaptive variational mode decomposition - Zhiwu Yu; Yaoming Li; Xiaoxue Du; Yanbin Liu (Biosystems Engineering, 2024)

Heavy metal pollution pressure in gold mines shows overall suppressed biochemical sulfur cycle - Shuaixian Mao; Qiancheng Zhao; Suya Ma; Yanbin Du; Jinshuai Shi; Jiacheng Zou; Ziliang Qiu; Caihong Yu (International Biodeterioration & Biodegradation, 2024)

Increasing biohydrogen production from swine wastewater influenced by anaerobic consortium and nickel ferrite nanoparticles - Jing Ye; Lihua Yu; Juanjuan Cao; Pei Zhao; Qin Zhang; Yanbin Li; Cheng Qian; khadija EI Galai; Mengdie Gao; Xinyu Yang (Fuel, 2024)

Imbibition characteristics and mechanisms of coal using digital image subtraction technique based on Micro-CT - Yanbin Yu; Jinhao Wang; Wenting Cui; Chengwei Gao; Yongtao Chen; Zihao Yuan (Fuel, 2024)

Biomineralization of heavy metals based on urea transport and hydrolysis within a new bacterial isolate, B. intermedia TSBOI - Xuesong Hu; Caihong Yu; Xianhong Li; Jiacheng Zou; Yanbin Du; David M. Paterson (Journal of Hazardous Materials, 2024)

Evolution rules of coal mesopore structure under the action of hydraulic coupling - Yanbin Yu; Ruoyu Mu; Weimin Cheng; Wenting Cui; Yongtao Chen (Bulletin of Engineering Geology and the Environment, 2024)

Obesogenic potentials of environmental artificial sweeteners with disturbances on both lipid metabolism and neural responses - Linhong Jiang; Zhenyang Yu; Yanbin Zhao; Daqiang Yin (Science of The Total Environment, 2024)

Mechanisms of microbial-driven changes in soil ecological stoichiometry around gold mines - Jinshuai Shi; Yanbin Du; Jiacheng Zou; Suya Ma; Shuaixian Mao; Wenyao Li; Caihong Yu (Journal of Hazardous Materials, 2024)

Microstructure evolution law and dissolution time effect of bituminous coal under acetic acid acidification: Based on Micro-CT image analysis - Yanbin Yu; Hao Xing; Weimin Cheng; Wenting Cui; Yongtao Chen (Fuel, 2024)

Exploring the accumulation capacity of dominant plants based on soil heavy metals forms and assessing heavy metals contamination characteristics near gold tailings ponds - Yanbin Du; Zhijun Tian; Yunfeng Zhao; Xinrong Wang; Zizhen Ma; Caihong Yu (Journal of Environmental Management, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Development of a new method framework to estimate the nonlinear and interaction relationship between environmental factors and soil heavy metals - Kaige Lei; Yan Li; Yanbin Zhang; Shiyi Wang; Er Yu; Feng Li; Fen Xiao; Fang Xia (Science of The Total Environment, 2023)

The impacts of farmer ageing on farmland ecological restoration technology adoption: Empirical evidence from rural China - Youping Yu; Jialan Zhang; Kuan Zhang; Dingde Xu; Yanbin Qi; Xin Deng (Journal of Cleaner Production, 2023)

Fracture and porosity evolution of coal under uniaxial compression: An in-situ X-ray tomography study - Yanbin Yu; Zhaoxu Qiu; Weimin Cheng; Qi Yang; Wenting Cui; Kang Rong; Yunfei Li (Geomechanics for Energy and the Environment, 2023)

Machine learning combined with Geodetector quantifies the synergistic effect of environmental factors on soil heavy metal pollution - Kaige Lei; Yan Li; Yanbin Zhang; Shiyi Wang; Er Yu; Feng Li; Fen Xiao; Zhou Shi; Fang Xia (Environmental Science and Pollution Research, 2023)

Numerical models reveal the suitable habitat area for the stock enhancement and release of marine organism larvae in Liaodong Bay - Xiaowei Hu; Wenhao Hou; Zhaojun Sheng; Yanbin Xi; Jiaxuan Yu; Ruijin Zhang (Frontiers in Marine Science, 2023)
Stock enhancement can effectively increase population sustainablility and improve fishery resources, making it crucial to discern the suitable habitats for stock enhancement based on efficiency considerations. In this paper, a comprehensive model was established to simulate environmental characteristics in the Liaodong Bay. A habitat suitability model was developed by considering the optimal growth conditions of the Portunus trituberculatus larvae (PTL). The coupled model showed that the optimal area for stock-enhancement with PTL occurs in late June, and the initial suitable habitat area identified represents 17.12% of the whole Liaodong Bay. Based on the larval migration model of PTL, the deviation between the larvae and the suitable habitat, as well as the actual available area for stock enhancement, were further determined after larval release in the initial suitable habitat. Only 33.67% of the larvae fulfilled the criteria of remaining within the suitable habitat for 95% of the time, and these larvae represented 6.19% of the whole area of Liaodong Bay. These findings means that the truly area available for stock enhancement is likely to be a very small portion of the entire bay, and more precise release of larvae will be necessary to ensure survival rates after release. Our study actually provides a methodological framework for the identification of suitable environment of stock enhancement. This methodology can provide technical guidance for the stock enhancement of marine larvae with same applicability for other bays, which in turn contributes to the sustainable use of marine ecosystem services and fisheries resources.

A framework for identifying propagation from meteorological to ecological drought events - Yihui Wang; Han Zhou; Jiejun Huang; Jiaxin Yu; Yanbin Yuan (Journal of Hydrology, 2023)

Divergent environmental responses of long-term variations in evapotranspiration over four grassland ecosystems in China based on eddy-covariance measurements - Han Zheng; Guirui Yu; Qiufeng Wang; Zhi Chen; Xianjin Zhu; Han Bao; Yuchen Sun; Panpan Niu; Yingnian Li; Peili Shi; Yanbin Hao; Fawei Zhang; et al. (Journal of Hydrology, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

Plasma-activated silicon–glass high-strength multistep bonding for low-temperature vacuum packaging - Mingzhi Yu; Libo Zhao; Yongliang Wang; Yong Xia; Yintao Ma; Yanbin Wang; Xiangguang Han; Yao Chen; Shun Lu; Guoxi Luo; Nan Zhu; Ping Yang; et al. (Chemical Engineering Journal, 2023)

A new configuration of Geiger-type cable domes with sliding ridge cables: Computational framework and structural feasibility investigation - Yu Xue; Yaozhi Luo; Yafeng Wang; Xian Xu; Hua-Ping Wan; Yanbin Shen; Wenwei Fu (Engineering Structures, 2023)

Unprecedented lake expansion in 2017–2018 on the Tibetan Plateau: Processes and environmental impacts - Yanbin Lei; Tandong Yao; Yongwei Sheng; Kun Yang; Wei Yang; Shenghai Li; Jing Zhou; Yaozhi Jiang; Yifan Yu (Journal of Hydrology, 2023)

Adaptation and removal mechanism of anion chromium and cation cadmium by sulfate-reducing bacteria culture systems under different carbon sources - Suya Ma; Qiancheng Zhao; Yanbin Du; Xuesong Hu; Jiale Zhang; Huadong Tan; Fuyuan Qiu; Caihong Yu (Journal of Environmental Chemical Engineering, 2023)

Phosphate adsorption using calcium aluminate decahydrate to achieve low phosphate concentrations: Batch and fixed-bed column studies - Peng Cheng; Yu Liu; Lei Yang; Qinting Ren; Xue Wang; Yanbin Chi; Honglin Yuan; Shaobin Wang; Yong-Xiang Ren (Journal of Environmental Chemical Engineering, 2023)

A binary-medium-based constitutive model for porous rocks - Yanbin Chen; Enlong Liu; Yanyang Yu; Huiwu Luo; Peishuai Chen (International Journal of Rock Mechanics and Mining Sciences, 2023)

The effect of cross-scale modulation of synoptic systems by the cold air pool on autumn nighttime rainfall over Hainan Island - Fei Wang; Shangfei Hai; Jie Feng; Xiadong An; Lijia Chen; Weihang Zhang; Yanbin Huang; Yingying Zhang; Yu Zhou; Lifang Sheng (Atmospheric Research, 2023)

Preparation of polyaluminium silicate sulphate by gravity supercritical method and its coagulation in oily sewage - Huili Zhang; Hailin Yu; Jinjun Deng; Lingmin Wu; Meijuan Hu; Yanbin Tong; Liqun Sun; Hongsheng Liu (Chemosphere, 2023)

Ecological risk assessment of trace metals in sediments and their effect on benthic organisms from the south coast of Zhejiang province, China - Zhengjia Zhao; Qiang Liu; Yibo Liao; Peisong Yu; Yanbin Tang; Qinghe Liu; Xiaolai Shi; Lu Shou; Jiangning Zeng; Quanzhen Chen; Jianfang Chen (Marine Pollution Bulletin, 2023)

Understanding synergistic mechanisms of silicate decorated polyaluminium chloride and organic polymer flocculation for enhancing polymer-flooding wastewater treatment - Lingmin Wu; Jinjun Deng; Hongsheng Liu; Hailin Yu; Huili Zhang; Yanbin Tong; Liqun Sun; Fankun Meng; Li Zhao (Process Safety and Environmental Protection, 2023)

Root cell wall remodeling: A way for exopolysaccharides to mitigate cadmium toxicity in rice seedling - Hong-yu Wei; Yi Li; Jiao Yan; Shuai-ying Peng; Sai-jin Wei; Yanbin Yin; Kun-tai Li; Xin Cheng (Journal of Hazardous Materials, 2023)

Application of the double-difference relocation method to acoustic emission events in high-pressure deformation experiments - Timothy Officer; Lupei Zhu; Ziyu Li; Tony Yu; David R. Edey; Yanbin Wang (Physics and Chemistry of Minerals, 2022)

Characterization, source apportionment, and assessment of volatile organic compounds in a typical urban area of southern Xinjiang, China - Xin Liu; Jianjiang Lu; Weijun Li; Zilong Liu; Yanbin Tong; Hao Chen; Junda Yu; YanZhou Ding (Air Quality, Atmosphere & Health, 2022)

Study on the effect of injection rate on the fracture initiation and extension in cement-sand slurry specimens - Shanwei Hu; Yanbin Yu; Weimin Cheng; Lei Zheng; Tong Lv (Bulletin of Engineering Geology and the Environment, 2022)

Study on seepage and wettability distribution of coal seam water injection based on electrical conductivity - Lei Zheng; Dewen Li; Yanbin Yu; Chengwei Gao; Yanpei Guo; Qilin Xin (Arabian Journal of Geosciences, 2022)

Numerical simulation study on the seepage characteristics of coal seam infusion effected by mining-induced stress - Yanbin Yu; Qilin Xin; Weimin Cheng; Jun Rui; Xin Zhang (Bulletin of Engineering Geology and the Environment, 2021)

The seepage characteristics of coal under the hydraulic-mechanics coupling conditions considering the variation of porosity - Yanbin Yu; Xin Zhang; Weimin Cheng; Xihui Yang; Lei Zheng (Arabian Journal of Geosciences, 2021)

Study on dynamic damage characteristics of coal under alternating hydraulic pressure - Qingfeng Xu; Yanbin Yu; Rulin Liu; Weimin Cheng; Haotian Yang (Bulletin of Engineering Geology and the Environment, 2021)

miR-9-5p facilitates hepatocellular carcinoma cell proliferation, migration and invasion by targeting ESR1 - Libing Wang; Mingxin Cui; Daming Cheng; Fengzhi Qu; Jingkun Yu; Yanbin Wei; Ling Cheng; Xiaotang Wu; Xiaogang Liu (Molecular and Cellular Biochemistry, 2021)

Spatially Overlapping Regions Show Abnormal Thalamo-frontal Circuit and Abnormal Precuneus in Disorders of Consciousness - Xiaoyan Wu; Qiuyou Xie; Xiaojin Liu; Huiyuan Huang; Qing Ma; Junjing Wang; Miao Zhong; Yanbin He; Chen Niu; Yan Chen; Feng Deng; Xiaoxiao Ni; et al. (Brain Topography, 2019)

Finger or Light: Stimulation Sensitivity of Visual Startle in the Coma Recovery Scale-Revised for Disorders of Consciousness - Feng Zhou; Hui Li; Kai Wang; Yanbin He; Yan Chen; Xiaoxiao Ni; Yechun Guo; Wei Lv; Jiechun Zhang; Qiuyou Xie; Ronghao Yu (Neuroscience Bulletin, 2018)

Visual Fixation Assessment in Patients with Disorders of Consciousness Based on Brain-Computer Interface - Jun Xiao; Jiahui Pan; Yanbin He; Qiuyou Xie; Tianyou Yu; Haiyun Huang; Wei Lv; Jiechun Zhang; Ronghao Yu; Yuanqing Li (Neuroscience Bulletin, 2018)

Joint structural and physiological control on the interannual variation in productivity in a temperate grassland: A data‐model comparison - Zhongmin Hu; Hao Shi; Kaili Cheng; Ying‐Ping Wang; Shilong Piao; Yue Li; Li Zhang; Jianyang Xia; Lei Zhou; Wenping Yuan; Steve Running; Longhui Li; et al. (Global Change Biology, 2018)
Given the important contributions of semiarid region to global land carbon cycle, accurate modeling of the interannual variability (IAV) of terrestrial gross primary productivity (GPP) is important but remains challenging. By decomposing GPP into leaf area index (LAI) and photosynthesis per leaf area (i.e., GPP_leaf), we investigated the IAV of GPP and the mechanisms responsible in a temperate grassland of northwestern China. We further assessed six ecosystem models for their capabilities in reproducing the observed IAV of GPP in a temperate grassland from 2004 to 2011 in China. We observed that the responses to LAI and GPP_leaf to soil water significantly contributed to IAV of GPP at the grassland ecosystem. Two of six models with prescribed LAI simulated of the observed IAV of GPP quite well, but still underestimated the variance of GPP_leaf, therefore the variance of GPP. In comparison, simulated pattern by the other four models with prognostic LAI differed significantly from the observed IAV of GPP. Only some models with prognostic LAI can capture the observed sharp decline of GPP in drought years. Further analysis indicated that accurately representing the responses of GPP_leaf and leaf stomatal conductance to soil moisture are critical for the models to reproduce the observed IAV of GPP_leaf. Our framework also identified that the contributions of LAI and GPP_leaf to the observed IAV of GPP were relatively independent. We conclude that our framework of decomposing GPP into LAI and GPP_leaf has a significant potential for facilitating future model intercomparison, benchmarking and optimization should be adopted for future data‐model comparisons.

Elevation‐dependent effects of climate change on vegetation greenness in the high mountains of southwest China during 1982–2013 - Jian Tao; Tongqing Xu; Jinwei Dong; Xiuqin Yu; Yanbin Jiang; Yangjian Zhang; Ke Huang; Juntao Zhu; Jianxin Dong; Yimin Xu; Shusheng Wang (International Journal of Climatology, 2018)
Effects of climate change on vegetation greenness have attracted considerable attention in the context of global change; however, the dependence of such climatic effects on elevation remains poorly understood. In this study, we examine the relationship between vegetation greenness change and climate change and, in particular, characterize how this relationship changes with elevation in the high mountains of southwest China by using the remotely sensed normalized difference vegetation index (NDVI), and observed temperature and precipitation data sets for the period of 1982–2013. The results show that vegetation exhibited a greening trend (slope: 0.0008 year −1 , p −1 , p −1 , p > 0.05). The vegetation greening and climate warming trends were stronger in the higher elevation plateaus than in the lower elevation mountains. Statistical analysis showed that temperature was the main driving factor on vegetation greening, and the driving effect was elevation‐dependent. A substantially more significant correlation between climate warming and vegetation greening was found in the higher elevation plateaus, which reveals a higher temperature sensitivity of these plateaus. In addition, a significant correlation between inter‐annual standard deviations of NDVI and precipitation during 1982–2013 was tracked over the entire study area.

Asymmetric reduction of ketopantolactone using a strictly (R)-stereoselective carbonyl reductase through efficient NADPH regeneration and the substrate constant-feeding strategy - Man Zhao; Liang Gao; Li Zhang; Yanbin Bai; Liang Chen; Meilan Yu; Feng Cheng; Jie Sun; Zhao Wang; Xiangxian Ying (Biotechnology Letters, 2017)

Climate‐driven global changes in carbon use efficiency - Yangjian Zhang; Guirui Yu; Jian Yang; Michael C. Wimberly; XianZhou Zhang; Jian Tao; Yanbin Jiang; Juntao Zhu (Global Ecology and Biogeography, 2014)
Aim Carbon use efficiency [net primary production ( NPP )/gross primary production ( GPP ) ratio] is a parameter related to the allocation of photosynthesized products by plants and is commonly used in many biogeochemical cycling models. But how this parameter changes with climates is still unknown. Faced by an aggravated global warming, there is a heightened necessity in unravelling the dependence of the NPP / GPP ratio on climates. The objective of this study was to examine how ongoing climate change is regulating global patterns of change in the NPP / GPP ratio. The study finding would elucidate whether the global vegetation ecosystem is becoming more or less efficient in terms of carbon storage under climatic fluctuation. Location The global planetary ecosystem. Methods The annual NPP / GPP ratio of the global terrestrial ecosystem was calculated over a 10‐year period based on M oderate R esolution I maging S pectroradiometer data and an ecosystem productivity model. The temporal dynamics of the global NPP / GPP ratio and their dependence on climate were investigated. Results The global NPP / GPP ratio exhibited a decreasing trend from 2000 to 2009 due to decreasing NPP and stable GPP over this period. The temporal dynamics of the NPP / GPP ratio were strongly controlled by temperature and precipitation. Increased temperature lowered the NPP / GPP ratio, and increased precipitation led to a higher NPP / GPP ratio. Conclusions The NPP / GPP ratio exhibits a clear temporal pattern associated with climatic fluctuations at a global scale. The associations of the NPP / GPP ratio with climatic variability challenge the conventional assumption that the NPP / GPP ratio should be consistent independent of environmental conditions. More importantly, the findings of this study have fundamental significance for our understanding of ongoing global climatic change. In regions and time periods experiencing drought or increased temperatures, plant ecosystems would suffer a higher ecosystem respiration cost and their net productivity would shrink.

Carbon emission trading system of China: a linked market vs. separated markets - Yu Liu; Shenghao Feng; Songfeng Cai; Yaxiong Zhang; Xiang Zhou; Yanbin Chen; Zhanming Chen (Frontiers of Earth Science, 2013)

More discussions for granger causality and new causality measures - Sanqing Hu; Yu Cao; Jianhai Zhang; Wanzeng Kong; Kun Yang; Yanbin Zhang; Xun Li (Cognitive Neurodynamics, 2012)

Quality differences between NILs of wheat variety Long 97-586 possessing HMW-GS 7+8 and 7 - LiLi Zhang; YanBin Zhang; JiLin Li; HaiBin Zhao; QingJie Song; HaiYang Yu; ChunLi Zhang; WenLi Xin; ZhiMin Xiao (Science China Life Sciences, 2010)